PERUBAHAN SOSIAL DAN PEMBARUAN HUKUM ISLAM PERSPEKTIF SADD AL-DZARI’AH - Gibtiah, Gibtiah; Fitriati, Yusida (Universitas Islam Negeri Raden Fatah Palembang, 2015)
Abstract: Social life is one of human nature that has innate.One characteristic of social life is the constant change in thecommunity. There is no society ever stop at a certain point of alltime, but constantly changing and moving forward. Changesthat occur sooner or later be able to change the joints staple ofpeople's lives. This paper explores social change and renewal ofIslamic law by using the method of determination of the law“sadd al dzari’ah”.ملخص: الحیاة الاجتماعیة ھي واحدة من طبیعة الإنسان الذي لدیھ الفطریة . واحدةمن سمات الحیاة الاجتماعیة ھي التغییر المستمر في المجتمع. لا یوجد أي مجتمعتتوقف أبدا عند نقطة معینة في كل العصور، ولكن تتغیر باستمرار، و تتحرك إلى الأمام. التغیرات التي تحدث عاجلا أو آجلا تكون قادرة على تغییر الأساسیة مفاصل حیاةالناس. وتبحث ھذه الورقة التغییر الاجتماعي والتجدید في الشریعة الإسلامیة باستخدامطریقة تحدید القانون.Kata kunci : metode penggalian hukum, sadd al-dzari’ah